Shifting STEM pedagogy through student voice: Faculty reflections on focus group data - Wolfmeyer, Mark; Kronenthal, Brian; Frye, Lisa; Lu, Yun (American Journal of STEM Education, 2026)
Improving undergraduate STEM education requires sustained attention to students’ lived experiences and the ways faculty respond to them. This qualitative study examines how faculty in computer science and mathematics engaged with anonymized student focus group data from students in an NSF S-STEM program. We took the opportunity to reflect on and adjust our teaching, mentoring, and advising practices. The focus group data revealed themes related to academic pacing, mentoring relationships, peer support, and the perceived disconnect of general education requirements, which faculty explored through structured, collaborative reflection. Findings illustrate how centering student voice can prompt meaningful pedagogical and programmatic shifts, highlighting a reflective, interdisciplinary, and reproducible model for fostering more responsive and inclusive STEM learning environments.